A combinatorial assessment of AlxCrCuFeNi2 (0 < x < 1.5) complex concentrated alloys: Microstructure, microhardness, and magnetic properties. (1st September 2016) - Borkar, T.; Gwalani, B.; Choudhuri, D.; Mikler, C.V.; Yannetta, C.J.; Chen, X.; Ramanujan, R.V.; Styles, M.J.; Gibson, M.A.; Banerjee, R.
Abstract: This article discusses a novel combinatorial approach for assessing composition-microstructure-microhardness-magnetic property relationships, using laser deposited compositionally graded Alx CrCuFeNi2 (0 < x < 1.5) complex concentrated alloys as a candidate system. The composition gradient has been achieved from CrCuFeNi2 to Al1.5 CrCuFeNi2 over a length of ∼25 mm, deposited using the laser engineered net shaping process from a blend of elemental powders. With increasing Al content, there was a gradual change from a fcc-based microstructure (including the ordered L12 phase) to a bcc-based microstructure (including the ordered B2 phase), accompanied with an increase in microhardness. Interestingly, with increasing paramagnetic Al content, saturation magnetization as well as coercivity increases and reaches a maximum value when x = 1.3, indicating the tunability of magnetic properties by a paramagnetic element in this alloy system. Such graded alloys are highly attractive candidates for investigating the influence of systematic compositional changes on microstructural evolution and concurrent physical and mechanical properties in complex concentrated alloys or high entropy alloys. Graphical abstract: